Inhibitors in haemophilia A: a perspective on clotting factor products as a potential contributing factor. (4th February 2016) - Mathew, P.; Dinter, H.; Church, N.; Humphries, T. J.; Kulkarni, R.
Abstract : Introduction: The occurrence of a neutralizing antibody in previously untreated patients (PUPs) with haemophilia A appears to be the result of an intricate interplay of both genetic and environmental factors. Recently, the type of factor VIII (FVIII) product used in the PUPs population has been implicated as a risk factor for inhibitor development. Aim: The aim of this review was to explore in a systematic manner potential hypotheses for the product‐related findings in these studies (i.e. differences in the expression system of the cell lines used to produce recombinant FVIII [rFVIII], differences in the administered antigen load or changes in clinical practice over time). Results: Review of the available clinical studies illustrates the high degree of variability for the risk of inhibitor development for the same products across different studies. Differences in cell lines or antigen load were not found to provide a reasonable explanation. Conclusion: The possibility of changes in clinical practice over time and patient selection bias (i.e. the preferential use of one product over another in patients at higher risk for inhibitors) offers a potential explanation and should be carefully considered when evaluating the studies.